Lignocellulosics in an ionic liquid, 1-ethylpyridinium chloride: reaction behavior and ion adsorption properties of corresponding humins - Ayako Miyata; Hisashi Miyafuji (Journal of Wood Science)
Abstract Herein, we studied the reaction behavior of cellulose, Japanese beech (Fagus crenata), and Japanese cedar (Cryptomeria japonica) in an ionic liquid, 1-ethylpyridinium chloride ([EtPy][Cl]), at 120 °C. Depolymerization occurred initially in all of the samples in a manner that formed low molecular weight compounds, followed by polymerization. The obtained polymers were black in color and ultraviolet-absorbing, and morphologically as well as chemically different from the raw materials, indicating that they were humins. These humins adsorbed cations in the order Ca2+ > Sr2+ > Cs+ > K+ > Na+, Li+. There was selectivity for adsorption of cations; cellulose-derived humins adsorbed Ca2+ particularly easily. The adsorptivity of humins was superior in the order cellulose-derived > beech-derived ≥ cedar-derived. The cation exchange capacity of cellulose-derived humins was higher than that of soil and comparable with that of natural zeolite, suggesting that humins obtained by [EtPy][Cl] treatment can be used as cation adsorbents.